Implementation of Triple Bottom Line: An Empirical Study of Medium, Medium-Large Businesses in the UAE - Theyyampattil, Mohammed Asif (Digital Repository of Theses, 2025)
Background This research examines the TBL (Triple Bottom Line) implementation challenges for medium and medium-large business enterprises in the UAE (United Arab Emirates). These distinctive cultural, environmental, economic, and regulatory circumstances provide an engaging situation for examining how companies balance the business’s environmental, social, and economic aspects. Purpose: The objective of this research is to identify and analyse the factors that influence the implementation of Triple Bottom Line (TBL) in the United Arab Emirates (UAE) business organisations. This study will investigate factors like cultural values, regional priorities, government policies, external and internal pressure factors, and laws of the land. By diving deep into these factors, this research aims to provide insights to businesspersons, policymakers, and business thought leaders across the world. Method of Research: This qualitative study is based on in-depth interviews with 24 business leaders across various sectors in the UAE. The data was analysed using thematic analysis to identify patterns and themes related to TBL implementation. Results: The conclusion emphasises the correct blend of Islamic ethics and global sustainability standards shaping the Triple Bottom Line practices in the UAE. Though the terminology of TBL is not very popular with UAE business leaders, they often see sustainable practices as essential for the long-term success of their business. Despite regulatory gaps and financial constraints, these practices are essential for the businesses’ long-term viability and brand reputation. Conclusion: This research gives a profound sketch of the business scenario and the outcomes of the TBL implementation in the UAE. The role played by the cultural values in driving the adoption of TBL in the region is clearly outlined in the study. Though businesses in the UAE face challenges in adopting TBL, they are increasingly willing to integrate TBL into the strategy. This positive approach is mainly because of the understanding that TBL could benefit them in the long run of the business. They also understand that the adoption will also contribute to national development goals besides improving competitiveness.